Impact of soaking, sprouting on antioxidant and anti-nutritional factors in millet grains - Bhuvaneshwari, G.; Nirmalakumari, A.; Kalaiselvi, S. (Journal of Phytology, 2020)
Commonly consumed millet types viz., Little millet, foxtail millet, pearl millet, finger millet, and Kodo millet were tested under two processing methods of soaking and germination at a different time point. Most popular processing practices adopted by Indian households were studied for their influence on the biochemical properties, antioxidant profile, and anti-nutritive factors. The results showed that the sprouting process showed a maximum influence on the antioxidant and anti-nutritive factors. The comparative analysis of the five millets suggested 24h soaking and 24h germination was found to be best for producing nutritionally enriched millet products. Tannin content decreases with an increase in germination. The reduction in tannin was about 50% in little millet (0.347 mg/g) and the highest was recorded in finger millet (2.07 mg/g). The highest amount of saponin content was found in pearl millet( 39.53 mg/g) followed by finger millet ( 34.86 mg/g) with 24 hr soaking and 24 hr germination. The phytase activity was found to be higher in little millet (61.520 u/kg) when prolonged soaking and germination. The DPPH assay showed sprouted foxtail millet grains contain more antioxidant activity (81.13%) when extent the period of soaking and germination.